1.solve for y
2x+4y=12
<u> </u><span><u> -2x -2x</u>
</span><u>4y</u>=<u>12-2x</u>
<u>4 4</u>
y=3-1/2x
step2 plug in y and solve for x
2x+8y=24
2x+8(3-1/2x)= 24
2x+24-4x=24
<u>-2x</u>=<u>0
</u><u>-2 -2</u>
x=0
last step plug in x and solve for y
y=3-1/2x(0)
y=3
Answer:
No, It is rational
Step-by-step explanation:
An number with a finite number of decimal point/numbers can be rational unlike numbers that repeat on forever like the number pi
On a given line, (on one side) there are a total of 180°
if one line in Problem #3 is bisected by a line, with one half X and the other 120°,
do 180° (the total) minus 120° which=60°
now the hard part, that line that bisected the first line is bisecting a line that is parallel to your second line, the one with <5 and <6
this means that the big angle formed in the first one with 120° is the same angle as in the second line, leaving <5 as 120°
which means <6 is 60°, like in the top part of the problem. You're basically flipping the top line upside down, I hope it helps.
Answer:
-3+(-6) = -9
Step-by-step explanation:
a negative 3 plus another negative 6 is a negative 9. Is just like if you borrow $3 from your friend and borrow $9 from another friend. That means you own two of your friends a total of $9. This can be mathematically illustrate as: -3 + (-6)= -9
Answer:
1) 25
2) 2
3) f(g(1)) = 42
Step-by-step explanation:
1) Given that f(x) = 4x^2 + 9
If x = -2
f(-2) = 4(-2)^2 + 9
f(-2) = 4(4) + 9
f(-2) = 16 + 9
f(-2) = 25
2) Given that f(x) = 4x - 6
y = 4x - 6
Replace y with x
x = 4y - 6
MAke y the subject of the forfmula
4y = x+ 6
y = (x+6)/4
SInce x = 2
f^(-1)(2) = (2+6)/4
f^(-1)(2) = 8/4 = 2
3) If f(x) = 6x and g(x) = x+6
f(g(x)) = f(x+6)
f(x+6) = 6(x+6)
Since x = 1
f(g(1)) = 6(1+6)
f(g(1)) = 6(7)
f(g(1)) = 42